LINC00472 suppresses non-small cell lung cancer progression via regulating miR-23a-3p/CCL22 axis: LINC00472 restrained NSCLC development - Yang, Sanhu; Liu, Yongshi; Li, Yan; Ji, Xiang; Yun, Yuhui; Yang, Guang; Liu, Honggang; Liang, Xiaohuang; Dang, Haizhou (Cellular and Molecular Biology, 2024)
Long non-coding RNA (lncRNA) LINC00472 has a close connection with the development of tumors. The aim was to explore the role of LINC00472 on NSCLC cell biological function in vivo and its potential mechanisms. The mRNA levels of LncRNA 00472 and microRNA-23a-3p, were determined by RT-qPCR. Cell Counting Kit-8, cell scratches and western blot assays were used to analyze the proliferation, migration and level of apoptosis-associated proteins. Luciferase reporter assay validates the binding between LINC00472/CCL22 and miR-23a-3p. LINC00472 and CCL22 were lowly expressed in NSCLC tissues and cells, while miR-23a-3p expression was upregulated. LINC00472 overexpression significantly depressed NSCLC cell cellular behavior, whereas promoting cell death. MiR-23a-3p could reverse these above-mentioned biological behavior changes caused by LINC00472 overexpression. Additionally, LINC00472 increased CCL22 expression through sponging miR-23a-3p. Knocking down CCL22 antagonized the inhibitory effect of LINC00472 on NSCLC cell survival. LINC00472 may reduce the cellular growth, and accelerate death of NSCLC through increasing CCL22 expression by targeting miR-23a-3p.